Modeling micro-cracking behavior of Bukit Timah granite using grain-based model - Peng, Jun (2020)
Rock strength and deformation behavior has long been recognized to be closely related to the microstructure and the associated micro-cracking process. A good understanding of crack initiation and coalescence mechanisms will thus allow us to account for the variation of rock strength and deformation properties from a microscopic view. This paper numerically investigates the micro-cracking behavior of Bukit Timah granite by using a grain-based modeling approach. First, the principles of grain-based model adopted in the two-dimensional Particle Flow Code and the numerical model generation procedure are reviewed. The micro-parameters of the numerical model are then calibrated to match the macro-properties of the rock obtained from tension and compression tests in the laboratory. The simulated rock properties are in good agreement with the laboratory test results with the errors less than ±6%. Finally, the calibrated model is used to study the micro-cracking behavior and the failure modes of the rock under direct tension and under compression with different confining pressures. The results reveal that when the numerical model is loaded in direct tension, only grain boundary tensile cracks are generated, and the simulated macroscopic fracture agrees well with the results obtained in laboratory tests. When the model is loaded in compression, the ratio of grain boundary tensile cracks to grain boundary shear cracks decreases with the increase in confining pressure. In other words, the results show that as the confining pressure increases, the failure mechanism changes from tension to shear. The simulated failure mode of the model changes from splitting to shear as the applied confining pressure gradually increases, which is comparable with that observed in laboratory tests. The grain-based model used in this study thus appears promising for further investigation of microscopic and macroscopic behavior of crystalline rocks under different loading conditions.